Rapid characterization schemes for surveillance isolates of vancomycin-resistant enterococci. - Sahm, D F (1997)
Surveillance cultures for vancomycin-resistant enterococci (VRE) and subsequent characterization of the isolates can be extremely burdensome and difficult. Therefore, efficient and reliable schemes for the characterization of surveillance isolates are needed. In this study, a commercial agar (bile esculin azide agar with 6 microg of vancomycin per ml [BEAA]; Remel, Lenexa, Kans.) was used in the initial screening step to establish relatively rapid (i.e., in < or = 24 h from the time of isolation) phenotype-based and PCR-based schemes for the detection and characterization of VRE. The phenotype-based scheme included Gram staining of growth on BEAA and subculture of cocci on sheep blood agar plates for vancomycin disk diffusion and pyrazinamidase (PYR) testing. For the PCR scheme, inocula for van gene detection were taken directly from the BEAA plates. The phenotypic approach was applied to 378 surveillance cultures that yielded growth on BEAA. Gram staining quickly eliminated gram-positive bacilli from further testing, and a negative PYR test classified 25 additional isolates as probable pediococci. A positive PYR test reliably identified 121 single-patient VRE isolates that included 83 Enterococcus faecium, 33 E. gallinarum, and 5 E. casseliflavus strains. The vancomycin inhibition zone size clearly distinguished VanA and VanB strains from VanC strains within 24 h of BEAA isolation. All VanA and VanB strains failed to produce zones of >6 mm, while only one VanC strain produced a zone of < 15 mm. Challenging this phenotypic scheme with 47 stock VRE isolates produced similar findings. In direct PCR analyses, false-negative vanA and vanB results occurred with 12% of the specimens. Many of the false-negative reactions also failed to produce an internal control product, which underscores the need for including control primers when a PCR scheme is used. In summary, the phenotype- and the PCR-based schemes provide efficient methods for characterizing VRE within 24 h of isolation.